Mechanistic insights into acid-affected hydrogenolysis of glycerol to 1, 3-propanediol over an Ir–Re/SiO2 catalyst. Issue 16 (2nd February 2022) - Zhou, Zheng; Ren, Xin; Cao, Yueqiang; Zhu, Yi-An; Zhou, Jinghong; Zhou, Xinggui
Abstract : This work traces the origins of acid effects on the glycerol hydrogenolysis to 1, 3-propanediol by experiments and DFT calculations. Abstract : Glycerol hydrogenolysis to 1, 3-propanediol is identified to follow the dehydration-hydrogenation pathway with the rate-determining step (RDS) of H* + OH* → H2 O* over an IrRe catalyst. The positive effects of solid acids are elucidated to originate from the reduced energy barrier of the RDS by H protons, while the negative ones of liquid acids are from excessively strong adsorption of anions.